Analisis Pengaruh Pengembangan dan Perubahan Kurikulum di Indonesia - Santikah, Santikah; Karimah, Siti Haura; Hidayani, Selnistia (Jurnal Manajemen dan Ilmu Administrasi, 2026)
Curriculum changes in Indonesia have been an ongoing phenomenon since independence. From the 1994 curriculum to the Merdeka curriculum, each change aims to improve the quality of education and meet the evolving needs of society. However, curriculum changes also pose challenges for teachers, students, and parents. This article analyzes the influence of curriculum development and changes in Indonesia, as well as their impact on the education system and society. This literature study identifies patterns and trends in curriculum development and change, and provides recommendations for improving the quality of the curriculum in Indonesia. The results show that curriculum changes can improve the quality of education, but also require adjustments and adaptations from all parties involved. Therefore, it is essential to understand the influence of curriculum changes and develop strategies to improve the quality of the curriculum in Indonesia. Thus, it is expected to improve the quality of education and meet the evolving needs of society. Curriculum changes must be accompanied by improvements in teacher quality, infrastructure, and other resources to achieve better educational goals. In addition, there needs to be cooperation between the government, schools, and the community to improve the quality of the curriculum and achieve national education goals.